A atudy on the optoelectronic properties of lead chalcogenides nanospheres using a combination of experimental and theoretical approach - Nur Farha, Shaafi; Saifful Kamaluddin, Muzakir; Mohd Fakhrul, Zamani Kadir; Shujahadeen, B. Aziz (Malaysian Journal of Microscopy, 2020)
Various morphologies and cluster geometries of lead chalcogenides (PbX, X = S, Se, Te) have been studied in the size range of 2 - 200 nm. The nanosized PbX clusters that are smaller than their exciton Bohr radius would experience deviation of optoelectronic properties (bandgap and energy levels) in comparison to that of the bulk. The multi-exciton generation (MEG) could be resulted upon expansion of energy levels of the quantum confined PbX; would expedite their application in photovoltaic field. The MEG would favor the increment of photo-generated current and therefore an increment of efficiency (η) of a photovoltaic device could be expected. The characterization of the electronic and emitting states of the quantum confined PbX is however received less attention. This paper aims to validate realistic models of PbX and establish a correlation between the validated models with the experimentally fabricated PbXs based on their optical properties. The narrow bandgap PbX models i.e., (PbS)n, (PbSe)n and (PbTe)n; which n = 4 - 80 were evaluated as realistic models using geometry optimizations and harmonic frequency calculations at the level of B3LYP functional and lanl2dz basis set. The PbX thin films were fabricated using thermal evaporator at vacuum pressure of 1.0 × 10-5 Torr. A nanosphere morphology of the yielded PbXs was observed using Field Emission Scanning Electron Microscopy (FESEM). The realistic models of (PbS)80, (PbSe)30 and (PbTe)50 were successfully established and validated as a basic building block of the fabricated thin film based on their crystal structure of the synthesized PbXs; supports the morphological observations made using FESEM